Therapeutic monitoring of vancomycin - doi 10.4025/actascihealthsci.v34i2.10617 (Acta Scientiarum. Health Sciences, 2012)
The present study aimed to characterize admitted patients in a public hospital in the Northwestern region of Paraná State, which were subject to therapeutic monitoring of vancomycin during 2007 and 2008. The data were obtained by a retrospective study of patients’ medical records, from where we separated the laboratory results, medical prescriptions, gender, age, and diagnosis of patients submitted to therapeutic monitoring. Of the total of 38 patients, only eight (21.1%) presented serum concentrations within recommended range, varying from 1.3 to 47.9 mg L-1. Concentrations above the reference value were observed in 22 patients (57.9%), and below the reference, in other eight patients (21.1%). The recommended serum concentrations at peak were obtained in only four patients (11.4%), higher than the recommended value in seven patients (20.0%), and lower, in 24 patients (68.6%). Only one patient (2.6%) presented serum concentration within the reference values at both high and low dosages. Therefore, the results evidenced the importance of therapeutic monitoring of vancomycin, individualizing the dose for each patient, and reducing toxic or subtherapeutic effects of this antimicrobial substance.